Characterization of the Fawn-Hooded Rat as a Model for Hemostatic Studies - Raymond, Sharon L; Jean Dodds, W (Thrombosis and Haemostasis, 1975)
A large colony of fawn-hooded (FH) rats, comprising five original families and six generations of their progeny, was developed for genetic and comparative studies of their bleeding tendency. The characteristics of the bleeding diathesis in these rats are similar to those originally reported in related rats by Tschopp and Zucker. FH rats have normal clot retraction, ADP-induced platelet aggregation and platelet ADP ; variable aggregation with collagen; minimal aggregation with adrenaline and cobra venom factor; and reduced platelet ATP, ATP/ADP ratio, serotonin content and 14C-serotonin release. In comparison to age- and sex-matched Wistar rats, FH rats have significantly prolonged partial thromboplastin time, shortened Russell’s viper venom time and increased factor X and XI levels. Other coagulation screening tests and specific assays for fibrinogen, plasminogen and factors VII, VIII and IX were normal. Some age- and sex-related differences in coagulation and other parameters were observed within each rat strain. Plasma proteins, glycoproteins and cerulo-plasmin (copper oxidase activity) showed no abnormalities, nor did initial studies of immunoglobulins and complement. However, FH rats have significantly lower glucose and higher cholesterol levels than comparable Wistar rats.